2015
DOI: 10.1002/elan.201500248
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activation of Silver Nanowires‐modified Pt Electrode by Cyclic Voltammetry in Comparison with Differential Pulse Voltammetry in Halide Determination

Abstract: Cyclic voltammetric (CV) and differential pulse voltammetric (DPV) measurements were carried out to assess the changes in electrode reactivity in halide determination with a silver nanowire‐modified platinum electrode. With DPV, successive voltammograms of the halide solution revealed progressive deterioration of the oxidation currents corresponding to Br− and Cl−, while those of I− increased largely. Comparatively, CV is stable and effective to remove precipitates due to the reduction process, in which, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This observation is also well supported by SWCNT-AgNW-resin hybrid film when it is used as an electrode material; and the shape of the curve is non-rectangular indicating the occurrence of redox reaction in presence of electrolyte ions from Na 2 SO 4 . This can be explained by the incorporation of highly conducting SWCNTs into the hybrid film, where it is postulated that the AgNW in the composite is become ionically very active at higher conductivity in presence of SWCNT, where the redox peak indicates a pseudo-capacitance derived from different oxidation states of Ag5758. Also, the excellent current response from the CV curve of the hybrid film indicates the occurrence of efficient faradaic redox reaction at higher electrons and ions transport rate.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is also well supported by SWCNT-AgNW-resin hybrid film when it is used as an electrode material; and the shape of the curve is non-rectangular indicating the occurrence of redox reaction in presence of electrolyte ions from Na 2 SO 4 . This can be explained by the incorporation of highly conducting SWCNTs into the hybrid film, where it is postulated that the AgNW in the composite is become ionically very active at higher conductivity in presence of SWCNT, where the redox peak indicates a pseudo-capacitance derived from different oxidation states of Ag5758. Also, the excellent current response from the CV curve of the hybrid film indicates the occurrence of efficient faradaic redox reaction at higher electrons and ions transport rate.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to EDL:Ag composites, it was observed that both of these processes took place. The faradaic process was observed through the presence of a characteristic Ag/Ag + redox couple [ 43 ], and the increasing mass ratio of AgNWs in the composite resulted in the expansion of the overall area under the CV curve, leading to the increase in CSC. The CSC of EDL:Ag 10:1, determined in this study, was almost 20 times higher than that of bare Pt substrates and 7 times higher than that of pristine EDL coated Pt electrodes, and was also higher than that for other previously reported biomaterial systems containing nanowires [ 44 ], indicating the high efficiency of EDL:Ag 10:1 in storing electric charge, and providing higher charges during electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrate that there is an electrochemical window wider than 1.40 V at different scanning rates, with an anodic stripping potential window lower than −0.82 V, which means that the detector is stable and suitable for iodine detection. 37 To verify the performance of the device on actual iodine samples, we investigated the sensing signals at different concentrations of iodine vapor with a wide range from 1 to 240 μM. One can see that the anodic peak current of iodine oxidation increases with increasing concentration of iodine, following a peak shift from −0.31 to −0.79 V (Figure 4C).…”
Section: An Obvious O−h•••i Hydrogen Bond Between the [Ch] + Cation A...mentioning
confidence: 96%
“…The CV curves of the IPIN-1-based electrochemical detector at various potential scan rates (a range from 10 to 500 mV s –1 ) are depicted in Figure B. The results demonstrate that there is an electrochemical window wider than 1.40 V at different scanning rates, with an anodic stripping potential window lower than −0.82 V, which means that the detector is stable and suitable for iodine detection . To verify the performance of the device on actual iodine samples, we investigated the sensing signals at different concentrations of iodine vapor with a wide range from 1 to 240 μM.…”
mentioning
confidence: 99%